VALUASI EKONOMI WISATA PULAU RUPAT KABUPATEN BENGKALIS, PROVINSI RIAU DENGAN METODE TRAVEL COST METHOD - Trisla Warningsih; Kusai, Deviasari; Lamun Bathara; Merry Manalu; Zahwa Syahzanani S (JFMR (Journal of Fisheries and Marine Research), 2021)
The research was conducted in July 2021 on Rupat Island, Bengkalis Regency, Riau Province. This study aims to estimate the economic value obtained from the value of consumer surplus by using the travel cost method. The data required includes primary and secondary data. The population used is tourists who visit Rupat Island tourism. Determination of respondents by accidental sampling with a total of 33 people. Data were analyzed by regression model. The results of the analysis show that the regression model obtained is Y= 3,0562 – 0,4068X1 + 0,5273X2 – 0,6815X3 – 0,3971X4 – 0,6056X5 – 0,0290X6, meaning that the demand for tourist visits to Rupat Island is positively influenced by X2 (income). The variables that have a negative effect are X1 (travel cost), X3 (age), X4 (distance), X5 (education) and X6 (gender). The average travel cost per visitor is IDR533,636.00,- per visit. The economic value of Rupat Island tourism is IDR1,507,554,457.51,- with a consumer surplus of IDR427,140.43,- per indivisual per visit